PUBLIC SERVICE MANAGEMENT IN THE NEW MONTA VILLAGE OFFICE, LAMBU SUB-DISTRICT, BIMA DISTRICT - irfadat, taufik (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2021)
Abstract The implementation of the Indonesian government system, both at the state and regional levels, is always changing. Of course the change in question is for the sake of creating an effective and efficient state administration in an actual and factual way in a better direction in accordance with current developments. The dynamics of state administration are always changing. Public service standards become an important issue in state administration, closely related to the position of the bureaucracy as a public servant and protector. As a symbol of public trust, the bureaucracy has the authority to interpret what is best for society. The objectives are to determine the management of services and to determine the disclosure of information on public services at the new monta village office, with a descriptive quantitative research method with a population of 1,268 respondents and a sample of 39 respondents. Based on the responses of respondents, who said that 20 people or 51.28% answered according to 12 people or 30.77%, those who answered were not suitable for 7 people or 17.95%, and those who answered did not match 0 people or 0%. That the majority of respondents gave variable assessments according to the principles of public service or had been implemented with a percentage of 76, 92% or 30 respondents who gave choices that were appropriat Keywords: management, service, public